2021
DOI: 10.3390/ijerph18030929
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ultrafine Particles and VOCs Emitted from a 3D Printer

Abstract: Currently, widely available three-dimensional (3D) printers are very popular with the public. Previous research has shown that these printers can emit ultrafine particles (UFPs) and volatile organic compounds (VOCs). Several studies have examined the emissivity of filaments from 3D printing, except glycol modified polyethylene terephthalate (PETG) and styrene free co-polyester (NGEN) filaments. The aim of this study was to evaluate UFP and VOC emissions when printing using a commonly available 3D printer (ORIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Particle number-based ER values (P-Trak data) for vHDPE, vLDPE, and vPP filaments ranged from 0.4 to 1.4 × 10 13 no./min for the normal-temperature prints (Table ). Literature values of particle ERs for ABS, PLA, nylon, polycarbonate, PETG, and several other types of filaments ranged from 10 8 to 10 11 no./min. ,, A comparison of results in Table to existing literature values indicated that the vHDPE, vLDPE, and vPP filaments emitted particles at higher number-based rates than ABS polymer. A prior study demonstrated that rats developed acute hypertension with a one-time exposure to emissions from 3-D printing with the ABS filament .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Particle number-based ER values (P-Trak data) for vHDPE, vLDPE, and vPP filaments ranged from 0.4 to 1.4 × 10 13 no./min for the normal-temperature prints (Table ). Literature values of particle ERs for ABS, PLA, nylon, polycarbonate, PETG, and several other types of filaments ranged from 10 8 to 10 11 no./min. ,, A comparison of results in Table to existing literature values indicated that the vHDPE, vLDPE, and vPP filaments emitted particles at higher number-based rates than ABS polymer. A prior study demonstrated that rats developed acute hypertension with a one-time exposure to emissions from 3-D printing with the ABS filament .…”
Section: Discussionmentioning
confidence: 86%
“…FFF 3-D printing with other polyethylenes such as PET and PETG primarily released xylene, toluene, styrene, and ethylbenzene, though none of these compounds were observed in the current study. 43,46 The literature from plastics extrusion (a process analogous to FFF 3-D printing) studies provides additional insights on possible emissions. Unwin et al reported that formaldehyde was quantifiable in the air of workplaces that extruded polyethylene polymers.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In turn, in a study by Azimi and col., 21 particle concentrations increased rapidly as soon as printing began, remained at this level for 10–20 minutes, and then decreased, but were higher than the background concentration. The release of most of the particles during the early stages of the FDM ® printing was documented in various investigations 111,125,149,150 . Yi and col 145 .…”
Section: Emissions From 3d Printing Devicesmentioning
confidence: 99%
“…The release of most of the particles during the early stages of the FDM ® printing was documented in various investigations. 111 , 125 , 149 , 150 Yi and col. 145 measured particle concentrations before (~1 h), during (~14 min), and after printing (~1 h). A few minutes after the start of printing, the particle number concentration increased rapidly to a maximum value of about 3×10 5 particles/cm 3 and decreased about 100 minutes after printing was completed.…”
Section: Emissions From 3d Printing Devicesmentioning
confidence: 99%
“…Previous studies have usually compared the measured concentrations of UFPs, their averages or their emission rates into the environment depending on the different types of filaments used in the printing process [5][6][7][8][9][10][11][12][13][14][15][16]. These measurements have shown that the composition of emissions from 3D printing is influenced by a number of factors, such as the chemical composition of the filament, its colour, the operating temperature of the print, the effect of the nozzle used, and the functionality of the printer [5][6][7][8][9][10][11][12][13][14][15][16]. The observed results are also influenced by the measurement scenario [11] or the type of instrumentation used [12].…”
Section: Introductionmentioning
confidence: 99%